2022
DOI: 10.1177/26335565221093569
|View full text |Cite
|
Sign up to set email alerts
|

Chronic condition clusters and associated disability over time

Abstract: Objectives Recent evidence shows that more complex clusters of chronic conditions are associated with poorer health outcomes. Less clear is the extent to which these clusters are associated with different types of disability (activities of daily living (ADL) and functional mobility (FM)) over time; the aim of this study was to investigate this relationship. Methods This was a longitudinal analysis using the National Health and Aging Trends Study (NHATS) ( n = 6179). Using latent class analysis (LCA), we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…For instance, frailty individuals commonly had a higher prevalence of chronic diseases than non-frailty people ( 56 ). People with chronic conditions demonstrated higher incidence rates of disability across all ADL items ( 57 59 ), our results also supported this view. Over time, the decline of BADL such as bathing, walking, toileting, dressing, transferring and eating, as well as IADL such as performing housework, shopping, cooking, taking medicine and financial management will increase.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…For instance, frailty individuals commonly had a higher prevalence of chronic diseases than non-frailty people ( 56 ). People with chronic conditions demonstrated higher incidence rates of disability across all ADL items ( 57 59 ), our results also supported this view. Over time, the decline of BADL such as bathing, walking, toileting, dressing, transferring and eating, as well as IADL such as performing housework, shopping, cooking, taking medicine and financial management will increase.…”
Section: Discussionsupporting
confidence: 86%
“…The inability to perform essential ADL leads to dependence on others and/or mechanical aids, and negatively affects daily activities, safe conditions and quality of life ( 78 ), all those increase slowness, weakness, low physical activity, and exhaustion resulting in frailty ( 79 , 80 ). In addition, the middle-aged and older participants with disability in ADL often suffer from chronic diseases ( 59 ), and the ability to take medicine in IADL may be restricted, which is not conducive to disease control, thus aggravating physical weakness and presenting frailty ( 3 , 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age has been found to be a strong associated factor of the multimorbidity patterns [ 11 , 12 ]. One study investigating rural community-resident aged 60 years and older revealed a four-cluster multimorbidity structure.…”
Section: Introductionmentioning
confidence: 99%